THE INFLUENCE OF EMOTIONAL INTELLIGENCE ON CAREER ADAPTABILITY MEDIATED BY CAREER DECISION SELF-EFFICACY : Pengaruh Kecerdasan Emosional terhadap Kesiapan Karir pada Mahasiswa Fakultas Ekonomi dan Bisnis dalam Mempersiapkan Karir dengan Efikasi Diri Keputusan Karir sebagai Variabel Mediasi - M. Iqbal; Rini Sarianti (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to analyze the effect of emotional intelligence on career adaptability in students of the Faculty of Economics and Business, Padang State University, with career decision self-efficacy as a mediating variable. Using a quantitative method with a survey approach, data were collected from 100 samples were used which were then processed using the SmartPLS v.4.1.0.2 application. The results of this study show that: (1) Emotional intelligence has a positive influence on career adaptability, (2) Emotional intelligence has a positive influence on career decision self efficacy, (3) Career decision self-efficacy has a positive influence on career adaptability, (4) Career decision self-efficacy mediates the influence of emotional intelligence on career adaptability